Acetylation of Conserved Lysines in the Catalytic Core of Cyclin-Dependent Kinase 9 Inhibits Kinase Activity and Regulates Transcription - Sabò, Arianna (American Society for Microbiology (ASM), 2008)
Promoter clearance and transcriptional processivity in eukaryotic cells are fundamentally regulated by the phosphorylation of the carboxy-terminal domain of RNA polymerase II (RNAPII). One of the kinases that essentially performs this function is P-TEFb (positive transcription elongation factor b), which is composed of cyclin-dependent kinase 9 (CDK9) associated with members of the cyclin T family. Here we show that cellular GCN5 and P/CAF, members of the GCN5-related N-acetyltransferase family of histone acetyltransferases, regulate CDK9 function by specifically acetylating the catalytic core of the enzyme and, in particular, a lysine that is essential for ATP coordination and the phosphotransfer reaction. Acetylation markedly reduces both the kinase function and transcriptional activity of P-TEFb. In contrast to unmodified CDK9, the acetylated fraction of the enzyme is specifically found in the insoluble nuclear matrix compartment. Acetylated CDK9 associates with the transcriptionally silent human immunodeficiency virus type 1 provirus; upon transcriptional activation, it is replaced by the unmodified form, which is involved in the elongating phase of transcription marked by Ser2-phosphorylated RNAPII. Given the conservation of the CDK9 acetylated residues in the catalytic task of virtually all CDK proteins, we anticipate that this mechanism of regulation might play a broader role in controlling the function of other members of this kinase family.